Pendampingan Pembuatan Kemasan Label Olahan Jamu Bathok Bu Tatik sebagai Implementasi Manajemen Branding dan Digital Marketing UMKM Kelurahan Wonorejo - Lia Rizqy Wulan Tari; Tri Kartika Pratiwi (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Carrying out innovation development in an MSME activity needs to be done especially in terms of branding and also marketing. The mentoring activity for making label packaging for processed herbal medicine for Bu Tatik is an implementation of branding management and digital marketing with an effort to improve and develop the business of an MSME. The problems faced by MSMEs are related to processed products that have unattractive packaging which is one of the problems experienced by partners even though their products are widely known in the market but their production capacity is also still small. In addition, the marketing carried out is still lacking, only relying on sales in the market. The purpose of Bu Tatik's herbal bathok mentoring activities is to increase productivity and develop product rebranding so that it has more selling value in the community. The implementation method used in this activity is assisting in making new logos and packaging stickers with attractive designs and developing promotional media through the application of digital marketing which includes creating business-specific websites and emails, creating Instagram social media accounts, verifying MSME locations on Google Maps, and making e-Catalog